2019
DOI: 10.3897/rrpharmacology.5.35529
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of liposomal dosage forms and hyperosmolar salines in experimental pharmacotherapy of acute lung injury

Abstract: Citation: Kulikov OA, Ageev VP, Marochkina EE, Dolgacheva IS, Minayeva OV, Inchina VI (2018) Efficacy of liposomal dosage forms and hyperosmolar salines in experimental pharmacotherapy of acute lung injury. Research Results in Pharmacology 5(2): 23-41. https://doi. AbstractIntroduction: Hypertonic sodium chloride solutions and liposomal drugs with pulmotropic effect are of great interest for the treatment of acute lung injury (ALI). The results of the studies on the efficacy of hypertonic solutions and liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Results showed that liposomes with average diameter of 350 nm efficiently targeted the lungs after intravenous administration and the liposomal formulations were effective in pharmacological repairment of ALI. [ 106 ] Moreover, liposomes have also been proposed to enhance the bioavailability of drug after oral administration. Liposome‐encapsulated spironolactone (Lipo‐SP) was prepared for ALI treatment via oral administration, which resulted in enhanced SP bioavailability with therapeutic/preventive potential for ALI by modulating the inflammatory phenotypes of circulating monocytes/lung macrophages.…”
Section: Respiratory Injuries and Disease Treatment With Nanomedicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that liposomes with average diameter of 350 nm efficiently targeted the lungs after intravenous administration and the liposomal formulations were effective in pharmacological repairment of ALI. [ 106 ] Moreover, liposomes have also been proposed to enhance the bioavailability of drug after oral administration. Liposome‐encapsulated spironolactone (Lipo‐SP) was prepared for ALI treatment via oral administration, which resulted in enhanced SP bioavailability with therapeutic/preventive potential for ALI by modulating the inflammatory phenotypes of circulating monocytes/lung macrophages.…”
Section: Respiratory Injuries and Disease Treatment With Nanomedicinesmentioning
confidence: 99%
“…[ 117 ] The excellent safety of liposomal components makes them highly appealing for drug delivery to the lung tissues. [ 106 ]…”
Section: Respiratory Injuries and Disease Treatment With Nanomedicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone has been highly regarded around the world for the new COVID-19 coronavirus infection [8] as an agent for battling intoxication, inflammation, and sclerotic changes in the lungs [9]. A liposomal form of dexamethasone that was studied for intravenous administration in models of lung pathology is certainly interesting [10,11]. However, scientific research on inhalation liposomal glucocorticosteroids is exceedingly rare [12].…”
mentioning
confidence: 99%